Case Report: Oxaliplatin-Induced Third-Degree Atrioventricular Block: First Discovery of an Important Side-Effect - Chen, Xi; Wang, Hui; Zhang, Zijin; Xu, Yan; An, Xuanqi; Ai, Xin; Li, Lin (Frontiers in Cardiovascular Medicine, 2022)
Background The adverse effects of anticancer therapy in patients with malignancies and cardiovascular diseases are complicated. Oxaliplatin is one of the most commonly used chemotherapy drugs for gastric and colorectal cancers, and oxaliplatin-induced cardiotoxicity has rarely been reported. Case Summary We report a 76-year-old man with adenocarcinoma of the esophagogastric junction and a 40-day history of non-ST-elevation myocardial infarction who exhibited a new third-degree atrioventricular block after oxaliplatin administration. We immediately withdrew oxaliplatin treatment and, to avoid future episodes, we implanted a permanent pacemaker for safety and added diltiazem hydrochloride. The third-degree atrioventricular block disappeared after oxaliplatin withdrawal. We detected no recurrence of the third-degree atrioventricular block in future chemotherapies. Conclusions This is the first reported oxaliplatin-induced third-degree atrioventricular block, likely mediated by coronary artery spasm. Cancer patients with acute coronary syndrome are a unique and vulnerable population, whom physicians should carefully evaluate and monitor during anticancer treatment. Remarkably, even the most common chemotherapy drugs can cause life-threatening cardiac adverse events.